The offer of corporate social responsibility and business ethics courses in university accounting undergraduate programs: A comparative analysis among administrative sciences - Buele Nugra, Irene; Pesantez, Andrea (Open Science Journal, 2021)
Business failures in the 1980s, in the United States, have prompted the undergraduate programs of Business Administration, Public Administration, Foreign Trade, Accounting and Auditing, Economics, Finance, Management and Leadership, Human Talent Management, Transportation Management, Business Management, Marketing, International Business and Tourism to strengthen the techniques and processes of education of the future professionals, based on the teaching of social responsibility and ethics. Hence, the main purpose of this research is to analyze the presence of subjects related to Business Ethics and Corporate Social Responsibility (CSR) at Universities and Polytechnic Schools that are within the National Public and Private classification, and which receive allocations and revenues from the State in Ecuador. For this purpose, null hypotheses (Ho) and alternative hypotheses (H1) have been proposed, obtaining significant statistical evidence in the analysis of 89 curricula of administrative science programs. The analysis shows that the offer of the 47 studied subjects of social responsibility, and 75 of ethics does not depend on whether the university is public or private to receive allocations and revenues from the State, but it does depend on the type of program or degree that is being offered. These higher education subjects are important to help, the future professional, remember his or her correct behavior, commitment, and actions in the company, in society, and in the environment.